Spillover Effect of Return and Volatility Between Digital and Traditional Assets - Sadewa, Putra; Andrian (Industrija, 2024)
This study aims to examine the spillover effects of return and volatility between three different assets (Bitcoin,Gold, and Nasdaq) using GARCH-ARMA models. The data is taken from monthly closing prices from January 2015 to February 2024 through Investing.com. The analysis focuses on understanding how these three assets interact regarding the spillover effect of return and volatility, particularly during periods of economic uncertainty. Our findings indicate that spillover effects of return are visible from Bitcoin to Nasdaq, Nasdaq to Bitcoin, and Nasdaq to Gold. In addition, spillover effects of volatility are visible from Gold to Bitcoin, Bitcoin to Nasdaq, Nasdaq to Bitcoin, and Nasdaq to Gold. Our finding highlights the dynamic relationship between traditional and digital assets, emphasizing Bitcoin’s potential role as a financial hedge likely to Gold and Nasdaq.